PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) MELALUI INTERAKSI DIGITAL SELLER SHOPEE MEBEL DUA PUTRA - Ika Fitri Aprilia; Sahri Aflah Ramadiansyah (Journal of Innovation Research and Knowledge, 2025)
The development of e-commerce in Indonesia provides a great opportunity for Micro, Small, and Medium Enterprises (UMKM) to expand their market reach. Shopee is one of the most widely used Marketplace platforms, equipped with digital communication features that enable sellers to build direct relationships with customers. However, the furniture sector faces its own challenges due to the large and heavy nature of its products. This certainly requires effective communication in the transaction process to ensure success. Previous studies have generally examined CRM implementation in the retail or fashion sector, but research focusing on the furniture business in marketplace platforms is still very limited. This shows the need to specifically explore how CRM is applied in product categories with unique characteristics, such as furniture. The purpose of this study is to examine how Customer Relationship Management (CRM) is implemented at Shopee Mebel Dua Putra using digital interactions while identifying the problems encountered. This study uses a descriptive qualitative method with interview, observation, and documentation techniques. The results show that CRM is implemented through three stages, namely acquisition, retention, and loyalty. However, implementation is still inconsistent due to limited digital literacy, lack of admin response, and suboptimal utilization of Shopee features. The novelty of this study lies in its focus on analyzing CRM practices in the furniture sector through Shopee as a marketplace platform, highlighting the communication strategies and challenges that differ from other UMKM sectors. findings emphasize the importance of a consistent digital communication strategy to strengthen trust, increase satisfaction, and foster customer loyalty in the context of Marketplace-based UMKM, particularly Shopee.